A recuperaç\~ao do desenvolvimentismo no regionalismo Latino-Americano - Rodrigo Alves Teixeira; Walter Antonio Desiderá Neto (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– This article aims to show that, by analyzing both the historical development of regional integration processes in Latin America and the political and economic ideas behind them, ECLAC's ideas, from the 1950's and 1960's, about what features Latin American integration should present - a developmental regionalism in opposition to a liberal one - have been recovered today. Thus, the article also intends to show the tension between these two kinds of regionalism in Latin American regional integration history.
Keywords: B22; F15; F42; F55; N16; O10; 330; regional integration; ECLAC; developmentalism; Latin American integration; economic thought